Optic nerve sheath fenestration for visual impairment in cerebral venous diseases - Xue, Xiao; Zhou, Chen; Gao, Yuan; Ji, Xunming; Zhang, Xuxiang (Frontiers in Neurology, 2023)
Objective Visual impairment is the most common clinical feature of cerebral venous sinus occlusion or cerebral venous thrombosis-induced intracranial hypertension, which can result in optic atrophy, leading to irreversible vision loss, visual field defections, and finally, permanent blindness. Papilledema is a typical early pathophysiological alteration in visual impairment. Optic nerve sheath fenestration (ONSF) has become increasingly accepted as an option to prevent or halt progressive visual loss owing to its low risk and complications. The objective of this study is to review the latest research progress on ONSF for the treatment of visual impairment related to cerebral venous diseases. Methods Study were searched following PRISMA guidelines based on three electronic databases (Pubmed, Embase and Medline-Ovid). We used the following keywords and variations as keywords to identify studies: “optic nerve sheath fenestration, papilledema, cerebral venous diseases, cerebral venous stenosis, cerebral venous thrombosis, idiopathic intracranial hypertension”. The publication date of studies was restricted between 1,872.1.1 and 2,021.12.31. The application of ONSF in papilledema due to cerebral venous diseases is reviewed. Additionally, the common surgical approaches as well as advantages and disadvantages are also described graphically. Results With the improvement of specific details of the ONSF procedure and surgical instruments, complications of ONSF have reduced and its safety has been significantly improved, although the number of clinically investigated cases in the literature remains low. Conclusion We recommend that ONSF should be considered as an imperative alternative to reduce or delay the visual morbidity of cerebral venous diseases, although there is yet no consensus on the optimal surgical timing.